What economics education is missing: The real world - Stephan Pühringer; Lukas Bäuerle (Cusanus Hochschule, Institut für Ökonomie und Institut für Philosophie, 2018)
The global financial crisis (GFC) led to increasing distrust in economic research and the economics profession, in the process of which the current state of economics and economic education in particular were heavily criticized. Against this background we conducted a study with undergraduate students of economics in order to capture their view of economic education. The paper is based on the Documentary Method, a qualitative empirical method, which combines maximum openness with regard to the collection of empirical material coupled with maximum rigor in analysis. The empirical findings show that students enter economics curricula with (1) epistemic, (2) practical or (3) moral/political motivations for understanding and dealing with real-world problems but end up remarkably disappointed after going through the mathematical and methods-orientated introductory courses. The findings further indicate that students develop strategies to cope with their disappointment - all of them relating to their original motivation. The theoretical contextualization of the empirical findings is based on the psychological concept of cognitive dissonance.
Keywords: A10; A11; A12; A20; B49; 330; Economic education; real-world orientation; cognitive dissonance; Global Financial Crisis; qualitative social research; Documentary Method